Does 77C-->G in PTPRC modify autoimmune disorders linked to the major histocompatibility locus? - Vorechovsky, I; Kralovicova, J; Tchilian, E; Masterman, T; Zhang, Z; Ferry, B; Misbah, S; Chapel, H; Webster, D; Hellgren, D; Anvret, M; Hillert, J; et al. (2001)
A 77G allele of the gene encoding CD45, also known as the protein tyrosine phosphatase receptor-type C gene (PTPRC), has been associated with multiple sclerosis (MS). Here we determine allele frequencies in large numbers of MS patients, primary immunodeficiencies linked to major histocompatibility complex (MHC) locus and over 1,000 controls to assess whether aberrant splicing of PTPRC caused by the 77C-->G polymorphism results in increased susceptibility to these diseases. Our results show no difference in the frequency of the 77G allele in patients and controls and thus do not support a causative role for the polymorphism in the development of disorders with a strong autoimmune component in etiology.